The role of engagement among farmers in developing farming knowledge: evidence from northern Thailand - CA Llones; S Suwanmaneepong (My University, 2021)
Abstract Several studies found science-based knowledge has only able to reach a small fraction of their desired recipient. To compensate for the lack of formal sources, farmers often relied on informal sources of knowledge within their farming community. This study investigates the role of farmer’s social engagement in developing farming knowledge and farmer’s decision-making. A structural equation modelling was used to test the hypothesised moderating role of social engagement among farmers on the effects of service access, training, and knowledge-sharing on farming knowledge. The study used the case of rice farmers in Northern Thailand, wherein a focus group discussion and a series of survey interviews were conducted. Study results found that social interactions among farming communities significantly moderated the effects of training and knowledge-sharing. The findings support the critical role of social engagement among farmers in increasing information flow and experiential knowledge exchange in developing farming knowledge. Furthermore, social interactions promote farming innovation and management practices through advice-seeking with other farmers. Hence, in supporting farming sustainability, extension support should also focus on network building among actors within the farming community and understand how farmers exchange experiential knowledge to compensate for the lack of formal sources of knowledge.
Keywords: Experiential Knowledge; Knowledge Sharing; Innovation and Socioeconomic Development